Bone loss in C57BL/6J‐OlaHsd mice, a substrain of C57BL/6J carrying mutated alpha‐synuclein and multimerin‐1 genes. Issue 1 (5th June 2017) - Liron, Tamar; Raphael, Bitya; Hiram‐Bab, Sahar; Bab, Itai A.; Gabet, Yankel
Abstract : The inbred mouse strain C57BL/6 is commonly used for the generation of transgenic mouse and is a well established strain in bone research. Different vendors supply different substrains of C57BL/6J as wild‐type animals when genetic drift did not incur any noticeable phenotype. However, we sporadically observed drastic differences in the bone phenotype of "WT" C57BL/6J mice originating from different labs and speculated that these variations are attributable, at least in part, to the variation between C57BL/6J substrains, which is often overlooked. C57BL/6J‐OlaHsd is a commonly used substrain that despite a well defined deletion in the alpha‐synuclein (Snca) and multimerin‐1 (Mmrn1) genes, was reported to display no obvious phenotype and is used as WT control. Here, we compared the bone phenotype of C57BL/6J‐OlaHsd (6J‐OLA) to C57BL/6J‐RccHsd (6J‐RCC) and to the original C57BL/6J (6J‐JAX). Using μCT analysis, we found that 6J‐OLA mice display a significantly lower trabecular bone mass compared to 6J‐RCC and 6J‐JAX. PCR analysis revealed that both the Snca and Mmrn1 genes are expressed in bone tissue of 6J‐RCC animals but not of 6J‐OLA mutants, suggesting either one or both genes play a role in bone metabolism. In vitro analysis demonstrated increase in osteoclasts number and decreased osteoblast mineralization in cells derived from 6J‐OLA compared with 6J‐RCC. Our data may shed light on unexplained differences in basal bone measurements between different research centers and reiterate the importance of specifying the exact substrain type. In addition, our findings describe the physiological role for Mmrn1 and/or Snca in bone remodeling. Abstract : The C57Bl/6J‐OlaHsd substrain commonly considered as wild‐type mice, display a low bone mass phenotype compared to the original 6J substrain. These differences are attributable to the physiological role of alpha‐synuclein and multimerin in osteoblast and osteoclast functions. These findings also reiterate the critical importance of using littermates as controls for transgenic mice.